Payment of Land and Building Acquisition Duty (BPHTB) for Buyers in Tuban Regency Based on Regional Regulation of Tuban Regency No. 8 of 2023 on Regional Taxes and Levies - Eni Nurul Hidayah (Eduvest - Journal of Universal Studies, 2026)
This paper discusses the payment of Land and Building Acquisition Duty (BPHTB) for buyers based on Tuban Regency Regional Regulation Number 8 of 2023 concerning Regional Taxes and Regional Levies, for which the author conducted a case study at the Tuban Regency BPKAD. The research problems addressed include analyzing the practice of BPHTB payments for sellers and buyers of land based on Tuban Regency Regional Regulation Number 8 of 2023 concerning Regional Taxes and Regional Levies, and examining the legal basis and mechanism for BPHTB collection as determined by the Tuban Regency Government through BPKAD. This study employs empirical legal research, which is a legal research method that uses primary data obtained directly through field research by examining legal reality in society that is, how the law operates in practice. The findings reveal that the practice of BPHTB payment for sellers and buyers of land under Regional Regulation of Tuban Regency Number 8 of 2023 concerning Regional Taxes and Regional Levies contains a contradiction between the content of the Perda and the legal reality in the field. The legal basis for BPHTB collection is Regional Regulation Number 8 of 2023 concerning Regional Taxes and Regional Levies, and the payment mechanism is conducted online through the portal provided by BPKAD.